Na meticilin odporni Staphylococcus aureus (MRSA): kako preprečiti njegovo širjenje v bolnišnicah in ambulantah - Trampuž, Andrej (Obzornik zdravstvene nege, 2001)
Methicillin-resistant Staphylococcus aureus (MRSA) has become a major nosocomial pathologen in hospitals and is increasingly important in long-term-care facilities. The epidemiology and microbiology of MRSA is reviewed. NRSA is usually introduced into an institution by a colonized or infected patient. The principal made of transmission is via the transpatient. The principal mode of transmission is via the transiently colonized hands of hospital personnel. A major reservoir is the nose of the health care workers and presents the source of endemic MRSA in hospitals. In addition, infection control measures are presented for acute-care hospitals and intensive care units.
Keywords: bacteria; bakterije; Cross infection; Handwashing; infekcije; Intensive care units; Methicillin resistance; Prevention and control; preventiva; stafilokoki; Staphylococcus aureus